Effects Of Advertisements On Brand Preferences: Proficiency Analysis Of Telecom Industries In Malaysia - Masood, Akbar (2008)
This research uses TV advertisement to examine three barands of cellular companies: Maxis, Digi and Celcom. The study first determines initial preferences for all three brands then analyzes the consumer indicated brand similarities and the effects of TV advertisement on brand preference.